Mass architecture and limitations - Николай Васильев (Проект Байкал, 2022)
Mass housing architecture requires special consideration. Both in the historical perspective and in the present, the designer needs to be aware of the factors affecting the design process implicitly, beyond the will of the client and the design brief. These factors lend themselves to systematization, and the main of them are considered in a historical perspective as essential to the formation and existence of the basic types of mass housing.